MEMBANGUN KEBERDAYAAN EKONOMI DI TENGAH KETIMPANGAN GENDER - Kurniawan, Borni; Mariana, Dina (Alam Lestari, 2012)
Women are a powerful creature. The double role was done. Work in the public sector was taken. The domestic sector was never left out. But, when related to the poverty and development discourses, women become to the most vulnerable groups. Women experience marginalization and gender injustice. The development which is permissive to the flow of capital to village eliminates womens accessibility to the basic needs that exist in the natural resources of village. The working worlds are also still not shown the equality in establishing job role between men and women. As a result, women are always in the minor position. Be thankful that in the part of the Nationwide there are still women village movements that build economic empowerment from inside so that the gender inequality gap can be minimized. The strategies that they employ to build a collective consciousness, economic networks, until the resistance to the market hegemony finally bear sweet fruit, where the women finally can enjoy the village resources.